A simple microwave-assisted synthesis of cobalt ferrite nanoparticles and its application for the determination of lead ions in rooibos (Aspalathus linearis) tea - Ayyildiz, Merve Firat; Karaman, Devrim Nur; Kartoglu, Bedrihan; Saylan, Meltem; Chormey, Dotse Selali; Bakirdere, Sezgin (ELSEVIER SCI LTD, 2023)
In this study, a magnetic sorbent assisted dispersive solid phase extraction (DSPE) method was used to preconcentrate lead ions from rooibos tea samples for determination by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS). Cobalt ferrite magnetic nanoparticles (CoFe2O4 MNPs) were synthesized by microwave assisted digestion. Limits of detection and quantification were calculated as 5.3 and 17.6 mu g/L, respectively, in a linear dynamic range of 20-800 mu g/L. The enhancement factor of the developed method was found to be 80folds when compared to the detection limit of the regular FAAS system. The percent recoveries obtained for rooibos tea samples spiked at different concentrations were in the range of 77 - 125%, with high repeatability as indicated by low standard deviations. The findings of the study demonstrated that the CoFe2O4 MNPs-based extraction method is a straightforward, fast, affordable, safe, and eco-friendly approach to qualifying/quantifying lead with high precision in the selected beverage sample.
Keywords: Flame atomic absorption spectrometer; Cobalt ferrite magnetic nanoparticles; Rooibos tea; Dispersive solid phase extraction; SOLID-PHASE EXTRACTION; MAGNETIC NANOPARTICLES; FOOD; PRECONCENTRATION; COFE2O4; WATER; PB; CD; SEPARATION; GRAPHITE; Chemistry; Food Science & Technology; Nutrition & Dietetics